Different filtering strategies of genotyping‐by‐sequencing data provide complementary resolutions of species boundaries and relationships in a clade of sexually deceptive orchids. Issue 2 (21st July 2019) - Cozzolino, Salvatore; Scopece, Giovanni; Roma, Luca; Schlüter, Philipp M.
Abstract: Ongoing hybridization and retained ancestral polymorphism in rapidly radiating lineages could mask recent cladogenetic events. This presents a challenge for the application of molecular phylogenetic methods to resolve differences between closely related taxa. We reanalyzed published genotyping‐by‐sequencing (GBS) data to infer the phylogeny of four species within the Ophrys sphegodes complex, a recently radiated clade of orchids. We used different data filtering approaches to detect different signals contained in the dataset generated by GBS and estimated their effects on maximum likelihood trees, global F ST and bootstrap support values. We obtained a maximum likelihood tree with high bootstrap support, separating the species by using a large dataset based on loci shared by at least 30% of accessions. Bootstrap and F ST values progressively decreased when filtering for loci shared by a higher number of accessions. However, when filtering more stringently to retain homozygous and organellar loci, we identified two main clades. These clades group individuals independently from their a priori species assignment, but were associated with two organellar haplotype clusters. We infer that a less stringent filtering preferentially selects for rapidly evolving lineage‐specific loci, which might better delimit lineages. In contrast, when using homozygous/organellar DNA loci the signature of a putative hybridization event in the lineage prevails over the most recent phylogenetic signal. These results show that using differing filtering strategies on GBS data could dissect the organellar and nuclear DNA phylogenetic signal and yield novel insights into relationships between closely related species.